The Comparison of Air Haji and Lumpo Dialect - Raflis Raflis; Rahma Dini (Jurnal Ilmiah Pendidikan Scholastic, 2026)
This research aims to analyze the dialectal differences between two areas in Pesisir Selatan Regency, namely Air Haji and Lumpo. The main focus of this research is to identify phoneme, lexical, and morphological variations that occur in the daily communication of native speakers. This study employs a qualitative descriptive method with a dialectological approach (Chambers and Trudgill, 2004) and a phonemic framework (Roach, 2009). Data were collected through in-depth interviews with four informants, two from Air Haji and two from Lumpo, as well as using a basic Morriswadesh vocabulary list and other semantic categories. The findings reveal 35 primary data points reflecting dialectal variation between the two areas: 15 phonological variations, 11 lexical variations, and 9 morphological variations. Phonological differences include the deletion and addition of phonemes, assimilation, vowel changes, syllable structure simplification, and lexical equivalence. Lexical differences are reflected in the use of different vocabulary to express the same meaning, while morphological differences involve variations in word forms and grammatical structures. These findings indicate that, although Air Haji and Lumpo are located within the same regency, geographical differences and local cultural factors contribute significantly to language variation